2002
DOI: 10.1152/ajpheart.00239.2002
|View full text |Cite
|
Sign up to set email alerts
|

Transmural gradients of cardiac myofiber shortening in aortic valve stenosis patients using MRI tagging

Abstract: Aortic valve stenosis impairs subendocardial perfusion with a risk of irreversible subendocardial tissue damage. A likely precursor of damage is subendocardial contractile dysfunction, expressed by the parameter TransDif, which is defined as epicardial minus endocardial myofiber shortening, normalized to the mean value. With the use of magnetic resonance tagging in two short-axis slices of the left ventricle (LV), TransDif was derived from LV torsion and contraction during ejection. TransDif was determined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 25 publications
6
78
1
1
Order By: Relevance
“…The relationship between torsion and strain can be approximated by a ratio of the peak torsion and the peak circumferential strain in the endocardial third of the myocardium, the torsion:shortening ratio. 6,38 This ratio is constant among healthy subjects of the same age and increases with healthy aging. 6,9 Both torsion and torsion:shortening ratio are measures of epicardial-endocardial interactions.…”
Section: Cardiac Taggingmentioning
confidence: 97%
“…The relationship between torsion and strain can be approximated by a ratio of the peak torsion and the peak circumferential strain in the endocardial third of the myocardium, the torsion:shortening ratio. 6,38 This ratio is constant among healthy subjects of the same age and increases with healthy aging. 6,9 Both torsion and torsion:shortening ratio are measures of epicardial-endocardial interactions.…”
Section: Cardiac Taggingmentioning
confidence: 97%
“…From the two series of tagged images, maps of horizontal and vertical displacement were determined (40). To relate timing of the tagged images to phases in the cardiac cycle, for each moment in each slice, the midwall radius was determined.…”
Section: Assessment Of LV Wall Strain Using Mrtmentioning
confidence: 99%
“…magnetic resonance tagging; finite-element model; cardiac mechanics; myofiber angle DEFORMATION OF THE CARDIAC WALL can be assessed noninvasively using ultrasound strain rate imaging (11) or magnetic resonance tagging (MRT) (4). The deformation patterns acquired may deviate from normal in the case of cardiac pathology, e.g., aortic stenosis, ischemia, or conduction disorders (39,40,43). The analysis of abnormal deformation patterns toward the underlying pathology is not straightforward: the relation between the change in the deformation pattern and the pathology is complex, and the criteria for normal and abnormal strain patterns have not yet been defined.…”
mentioning
confidence: 99%
“…Furthermore, the torsion-to-shortening ratio (TSR) parameter was calculated for both rats and humans. TSR indicates the transmural distribution of contractile myofibers and their function (2,5,29). For example, it has been found that TSR is different for aortic stenosis patients than for normal subjects due to the change in the transmural distribution of the myocardial fibers resulting from a remodeling process (29).…”
mentioning
confidence: 99%